1997
DOI: 10.1097/00003446-199710000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Functions for the CID W-22 and NU Auditory Test No. 6. Materials Spoken by the Same Speaker

Abstract: The equivalence was determined for the W-22 and NU No. 6 lists recorded with the same carrier phrase and by the same speaker (Auditec compact disc). For presentation, the lists were interleaved to form lists of 100 words. In Experiment 1, the materials were presented in quiet (0 to 30 dB HL) and in 60 dB SPL speech-spectrum noise (35 to 65 dB HL) at 5 dB intervals to 24 subjects with normal hearing. In Experiment 2, the materials were presented at two levels 10 dB apart to 24 subjects with sensorineural hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 2 publications
3
24
0
Order By: Relevance
“…The means that the slopes from the 20% to 80% range for the Turkish monosyllabic psychometric functions are close to those of word recognition test materials that have been reported in other Oyler [37] stated that they were 4.8%/dB and 4.4%/dB. A comparison of the mean slopes for English and other languages is presented in Table 7 [2, 9, 16, 36 -43] .…”
Section: Word Recognition Scores (%)supporting
confidence: 69%
See 1 more Smart Citation
“…The means that the slopes from the 20% to 80% range for the Turkish monosyllabic psychometric functions are close to those of word recognition test materials that have been reported in other Oyler [37] stated that they were 4.8%/dB and 4.4%/dB. A comparison of the mean slopes for English and other languages is presented in Table 7 [2, 9, 16, 36 -43] .…”
Section: Word Recognition Scores (%)supporting
confidence: 69%
“…Han et al [16] 4.1 English NU-6, Beattie et al [36] 4.2 English CIDW-22, Beattie et al [36] 4.6 English NU-6, Wilson and Oyler [37] 4.4…”
Section: Mandarinmentioning
confidence: 99%
“…Beattie et al (1977) reported a mean slope of 4.2 %/dB for the NU-6 word lists and a mean slope of 4.6 %/dB for the CID W-22 word lists. A more recent study found that the recordings from the Auditec of St. Louis CD, NU-6 and CID W-22 word lists had means of 4.4 %/dB and 4.8 %/dB, respectively (Wilson & Oyler, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Shi and Zaki (2014) demonstrated comparable functions for monolinguals and English-dominant bilinguals (with slopes approximately 4% per dB, similar to the monolingual average reported by Wilson & Oyler, 1997), but bilinguals who were dominant in their native language had significantly lower slopes (a flatter function) than the other two groups of listeners (by 0.7%-1.0% per dB). The latter finding suggests that some bilinguals' psychometric functions on the English test grow at a significantly slower rate than the monolingual average.…”
Section: Performance Across Snrsmentioning
confidence: 71%
“…The psychometric function for the NU-6 word recognition test has been established in quiet and in noise for monolinguals (e.g., Wilson & Oyler, 1997) and in noise for bilinguals by Shi and Zaki (2014). Shi and Zaki (2014) demonstrated comparable functions for monolinguals and English-dominant bilinguals (with slopes approximately 4% per dB, similar to the monolingual average reported by Wilson & Oyler, 1997), but bilinguals who were dominant in their native language had significantly lower slopes (a flatter function) than the other two groups of listeners (by 0.7%-1.0% per dB).…”
Section: Performance Across Snrsmentioning
confidence: 99%